SPECYFIKA LINGWO- I PRAWNOKULTUROWA W WYBRANYCH SZWAJCARSKICH AKTACH KONSTYTUCYJNYCH Z UWZGLĘDNIENIEM PERSPEKTYWY TRANSLACYJNEJ - Iluk, Łukasz (Comparative Legilinguistics, 2021)
The subject of the analysis is linguaculture expressing linguistic and cultural differences occurring in every language of law. They relate to vocabulary and editing principles of law acts. It seems that preserving such differences in the target translation makes it possible to reveal specific legislation trends of a given country, which express political motivation. Their preservation in the translated text requires good knowledge of law and in-depth comparative analysis. The focus of the analysis in this text is on the expression of gender in the law texts and specifically, on the translation of feminatives and legal names relevant for cultural dimension of a given law system.